Γαμηλιότητα και διάλυση των έγγαμων συμβιώσεων στην Ελλάδα: μια πρώτη δημογραφική προσέγγιση - Κοτζαμάνης, Βύρων (The Greek Review of Social Research, 1997)
In this article we examine the diachronical changes of the intensity and of the calendar of marriages and divorces. It is a classical demographic analysis aiming at giving answers to some simple, but fundamental questions as: ■ do the successive cohorts of Greek women get married more or less, at a younger or at a more mature age? ■ do their marriages break off more easily or not, and after how many years of living together? ■ what are the emerging tendencies and the immediate perspectives? ■ finally, will the dominant in our country up today model of nuclear family, based on marriage and on the «endurance» of marriage, preserve its universality or will it survive in coexistence with other models more or less marginal, as it happens in most European countries? The answers to the above questions come before the searching and stating of the determinants of any changes in these fìelds, factors which constitute the basic objective of the sociology of family.